PERANCANGAN APLIKASI E-LEARNING BERBASIS EKSPLORASI UNTUK MENGEMBANGKAN ASPEK PSIKOMOTOR SISWA DI MASA PANDEMI - Muji Juherwin (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2023)
During the Covid-19 pandemic, learning activities were mostly carried out online. This method leaves a gap, especially in the psychomotor development of students. This study focuses on the development of a learning application. The goal of this application is to help students increase their psychomotor aspects. This research was started by getting input from teachers regarding the need for developing worksheets that support students' psychomotor development. Inputs are filtered by the following criteria; support psychomotor development, based on exploratory activities, and the balance between screen time and outdoor activities. From this input, we figure out that the main components in the application should focus on student skills, empowering the environment, column for activity output, according to context, and giving students the experience to find the basic concepts for themselves. From this input, we develop a website as a learning application. This website has four main entities; missions, explorers (students), givers (teachers who make missions), and experts (assessors) who will assess whether the mission is applicable, following the spirit of exploration, and safe. An assessment of students' responses to the application with five scales (dislike 1 – 5 like) results in the average level of liking and ease of use of users in using the application was 4.07.